2019
DOI: 10.1111/jipb.12803
|View full text |Cite
|
Sign up to set email alerts
|

Specifying the role of BAK1‐interacting receptor‐like kinase 3 in brassinosteroid signaling

Abstract: Brassinosteroids (BR) are involved in the control of several developmental processes ranging from root elongation to senescence and adaptation to environmental cues. Thus, BR perception and signaling have to be precisely regulated. One regulator is BRI1‐associated kinase 1 (BAK1)‐interacting receptor‐like kinase 3 (BIR3). In the absence of BR, BIR3 forms complexes with BR insensitive 1 (BRI1) and BAK1. However, the biophysical and energetic requirements for complex formation in the absence of the ligand have y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
(161 reference statements)
0
19
0
1
Order By: Relevance
“…As revealed by the RLP44 interaction pattern, signaling integration and ramification is realized at the level of the receptor complex in the plasma membrane. Additional examples are the interaction of the BRI1-BAK1 complex with G-proteins to mediate sugar-responsive growth (Peng et al, 2018), with the proton pumps of the P-ATPase type to regulate plasma membrane hyperpolarization and wall swelling that precede cell elongation growth (Caesar et al, 2011), and with the BAK1-interacting receptor-like kinase 3 (BIR3) that represses the activity of the complex in the absence of BR (Imkampe et al, 2017;Hohmann et al, 2018;Großeholz et al, 2019). In addition, BRI1 phosphorylates a homolog of the mammalian transforming growth factor-b (TGF-b) receptor interacting protein/ eIF3 eukaryotic translation initiation factor subunit TRIP-1 (Ehsan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As revealed by the RLP44 interaction pattern, signaling integration and ramification is realized at the level of the receptor complex in the plasma membrane. Additional examples are the interaction of the BRI1-BAK1 complex with G-proteins to mediate sugar-responsive growth (Peng et al, 2018), with the proton pumps of the P-ATPase type to regulate plasma membrane hyperpolarization and wall swelling that precede cell elongation growth (Caesar et al, 2011), and with the BAK1-interacting receptor-like kinase 3 (BIR3) that represses the activity of the complex in the absence of BR (Imkampe et al, 2017;Hohmann et al, 2018;Großeholz et al, 2019). In addition, BRI1 phosphorylates a homolog of the mammalian transforming growth factor-b (TGF-b) receptor interacting protein/ eIF3 eukaryotic translation initiation factor subunit TRIP-1 (Ehsan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As revealed by the RLP44 interaction pattern, signalling integration and ramification is realised at the level of the receptor complex in the plasma membrane. Additional examples are the interaction of the BRI1-BAK1 complex with G-proteins to mediate sugar-responsive growth (Peng et al , 2018), with the proton pumps of the P-ATPase type to regulate plasma membrane hyperpolarisation and wall swelling that precede cell elongation growth (Caesar et al , 2011) and with the BAK1-interacting receptor-like kinase 3 (BIR3) that represses the activity of the complex in the absence of BR (Großeholz et al , Imkampe et al , 2017, Hohmann et al , 2018)(Imkampe et al, 2017; Hohmann et al, 2018; Großeholz et al, 2019). In addition, BRI1 phosphorylates a homolog of the mammalian TGF-β receptor interacting protein/eIF3 eukaryotic translation initiation factor subunit TRIP-1 (Ehsan et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Despite lack of experimental evidence or structural information, it has been widely accepted that stable association of the extracellular domains of BRI1 and BAK1 brings their cytoplasmic domains into close proximity, thus permitting cross phosphorylation, especially at Ser 1044 of BRI1 and Thr 450 of BAK1 within their respective activation loop, and subsequent activation of both kinases [ 45 , 46 , 59 ]. A recent structural modeling study suggested that the cytoplasmic domains of BRI1 and BAK1 could weakly interact independently of BR binding to their extracellular domains [ 60 ]. However, it is important to point out that the structural models of the kinase domains of BRI1 and BAK1 used for the modeling study were derived from autophosphorylated and activated kinase domains with stabilized αC-helixes and activation segments.…”
Section: Bri1 the Br Receptormentioning
confidence: 99%